2018
DOI: 10.2478/cjf-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Otolith Morphology and Morphometry in Eight Juvenile Fish Species in the Coastal Eastern Adriatic

Abstract: Sagittae otoliths of eight juvenile species: Boops boops, Diplodus vulgaris, Diplodus puntazzo, Sarpa salpa (family Sparidae), Liza ramada, Liza aurata (family Mugilidae), Atherina boyeri, Atherina hepsetus (family Atherinidae) were analysed and compared using descriptive morphological characters and morphometric indices. The noticeable differences among the otoliths of the investigated species are in their overall shape, margins (i.e. irregular, sinuate or crenate) and anterior region. Otolith shape varied fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Furthermore, some authors have reported that age and sex may induce a significant difference in the otolith shape in fish stocks . As a result, Ferri et al (2018) found that the otolith shape is significantly different in juveniles from that in adults due to differences in the hearing function. However, it is noteworthy to mention herein that the sampling was only restricted to adult samples of B. boops to eliminate the confounding effect of allometric growth on the otolith form (Mejri et al 2020).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Furthermore, some authors have reported that age and sex may induce a significant difference in the otolith shape in fish stocks . As a result, Ferri et al (2018) found that the otolith shape is significantly different in juveniles from that in adults due to differences in the hearing function. However, it is noteworthy to mention herein that the sampling was only restricted to adult samples of B. boops to eliminate the confounding effect of allometric growth on the otolith form (Mejri et al 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Also, Ider et al (2017) analyzed the variability of otolith shape in three populations of B. boops collected from the Algerian coast and observed a significant difference between the left and right otoliths and added that the shape is influenced by the fish length and the sampling location, but it is not related to sex and age. In addition, Ferri et al (2018) studied the variability of the otolith morphology and morphometry in six juvenile specimens collected from the eastern coastal Adriatic region and recorded variations in the sagittae shape, margins, and anterior region among the studied juveniles. Moreover, Mahé et al (2019) analyzed the directional bilateral asymmetry of otoliths in specimens collected from 11 geographical regions from the Canary Islands to the Aegean Sea using elliptical Fourier descriptors and found a significant otolith bilateral asymmetry at the global scale and non-significant asymmetry at the scale of sampling locations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An advantage of otolith shape analysis is that if the discrimination between species is statistically significant, it can be more advantageous as a monitoring tool, because of its relatively low cost, easy preparation procedures (Christensen et al ., 2018) and most importantly for improving accuracy and precision in determining age. Otolith shape analyses have been successfully applied to a number of species (Capoccioni et al ., 2011; Škeljo & Ferri, 2012; Ferri et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%